BLOOD GLUCOSE AS A DOMINANT FACTOR OF HYPERCHOLESTEROLEMIA - ratu ayu; Fani Widiartha (Jurnal Kesehatan Komunitas, 2020)
Cholesterol is a major factor of atherosclerosis. Hypercholesterolemia may increase the risk of developing coronary heart disease, myocardial infarction, cerebral thrombosis, ischemia, and other serious illnesses and even death. The aim of this study is to determine the dominant factors that affect the incidence of hypercholesterolemia in adult patients at Puskesmas Bojong Gede Bogor 2017. Primary data collected using cross-sectional method in Puskesmas Bojong Gede Bogor to 85 respondents aged 25-64 years. The results found that the prevalence of hypercholesterolemia is 62.4%. There was a significant relationship between blood glucose and waist circumference with hypercholesterolemia. Blood glucose level is the dominant factor for hypercholesterolemia. Health agencies are expected to be more active to do health promotion and education about healthy life and do routine health checks.